High quantitative and no molecular differentiation of a freshwater snail ( Galba truncatula ) between temporary and permanent water habitats - ELODIE CHAPUIS; SANDRINE TROUVE; BENOIT FACON; LOÏC DEGEN; JEROME GOUDET (Molecular Ecology, 2007)
We investigate the variation in quantitative and molecular traits in the freshwater snail Galba truncatula, from permanent and temporary water habitats. Using a common garden experiment, we measured 20 quantitative traits and molecular variation using seven microsatellites in 17 populations belonging to these two habitats. We estimated trait means in each habitat. We also estimated the distributions of overall genetic quantitative variation ( Q ST ), and of molecular variation ( F ST ), within and between habitats. Overall, we observed a lack of association between molecular and quantitative variance. Among habitats, we found Q ST > F ST , an indication of selection for different optima. Individuals from temporary water habitat matured older, at a larger size and were less fecund than individuals from permanent water habitat. We discuss these findings in the light of several theories for life‐history traits evolution.